Strategi Pengembangan Industri Pariwisata (Studi Kasus Objek Wisata Pulau Rukui Kabupaten Aceh Tamiang) - Nurlina, Nurlina; Pratama, Yolanna Shofa; Andiny, Puti (Jurnal Samudra Ekonomi dan Bisnis, 2022)
The study aims to determine the tourism industry development strategy on Rukui Island of Aceh Tamiang Regency. The population is tourist visitors, Regional Development Planning Agency, and Tourism, Youth and Sport Office. The analysis method uses SWOT. The results show that the main strength factor is that the community supports the government in developing tourism objects; the weakness is that the facilities are not yet available (public toilets and lounging huts); the opportunity is that this tourist attraction is able to encourage economic activity, create jobs for the surrounding community, the number of tourists who want to visit Rukui Island; and, the threat is the lack of awareness of tourists to maintain cleanliness. The recommended strategies are to increase promotion through various print and electronic media; improve facilities, infrastructure and supporting infra-structure; government and private investors joint together to create new innovations; and, the government cooperates with the community to provide socialization and guidance so as to improve the quality of human resources.